A woman's guide to claiming space : stand tall, raise your voice, be heard - Vancort, Eliza (Berrett-Koehler Publishers, Inc., 2021)
"For too long, women have been told to confine themselves -- physically, socially, and emotionally. Eliza VanCort says now is the time for women to stand tall, raise their voices, and claim their space. Women fight the pressure to make themselves small in private, professional, and public spaces. Eliza VanCort, a teacher, consultant, and speaker, provides the necessary tools for women to rewrite the rules and create the stories of their choosing safely and without apology. VanCort identifies the five key behaviors of all "Space Claiming Queens": use your voice and posture to project confidence and power, end self-sabotage, forge connections, neutralize unsafe spaces, and unite across differences. Through personal narrative, research, and actionable strategies, VanCort provides how-tos on combating challenges like antimentors and microaggressions and gives advice for building up your "old girls" club, asking for what you're worth, and owning your space without apology. Bold, fun, and enlightening, this book is birthed from VanCort's incredible story. Having a mother with schizophrenia forced VanCort to learn to be small and invisible at an early age, and suffering a traumatic brain injury as an adult required her to rethink communication from the ground up. Drawing on these experiences, and those of real women everywhere, VanCort empowers women to claim space for themselves and for their sisters with courage, empathy, and conviction because "when we rise together, we rise so much higher."--